EXPONENTIAL DECAY OF WAVE EQUATION WITH A VISCOELASTIC BOUNDARY CONDITION AND SOURCE TERM - Carrera Barrantes, Víctor Emilio (2008)
In this paper we are concerned with the stability of solutions for the wave equation with a viscoelastic Boundary condition and source term by using the potential well method, the multiplier technique and unique continuation theorem for the wave equation with variable coefficient.